Características fitométricas de trigo adubado com nitrogênio : potássio e nitrogênio : enxofre no cerrado mato-grossense - Paula, Raphael Pereira França de (2020)
The wheat crop has been cultivated mainly in the southern region of Brazil, with the potential to expand to other regions such as the Midwest. High yields have been achieved in this region, due to genetic improvement, where cultivars are developed adapted to the region's climate and through fertilization management. The Cerrado soils have low natural fertility, however, with the correction of soil acidity and the application of fertilizers there is an increase in the productivity of agricultural crops. In this context, the objective was to evaluate the phytometric characteristics of irrigated wheat fertilized with combinations of nitrogen and potassium and nitrogen and sulfur in two consecutive years of cultivation in the Cerrado of Mato Grosso. Two experiments were carried out simultaneously: experiment 1: nitrogen / potassium combinations and experiment 2: nitrogen / sulfur in the years 2018 and 2019, in the experimental area of the Federal University of Mato Grosso, Campus de Rondonópolis. The statistical design used was in randomized blocks in a fractional 52 factorial scheme. In the first experiment five doses of nitrogen (0, 70, 140, 210 and 280 kg ha-1 ) were used with five doses of potassium (0, 50, 100, 150 and 200 kg ha-1 ) and in the second experiment five doses were used nitrogen (0, 70, 140, 210 and 280 kg ha-1 ) with five sulfur doses (0, 25, 50, 75 and 100 kg ha-1 ), with four replications. The analyzed variables corresponding to the growth and development of wheat plants occurred at 15, 30 and 45 days after emergence (DAE), evaluating plant height, number of leaves, number of tillers, lodging, ear length, ear diameter and stalk length in the two years of cultivation. The response variables were subjected to analysis of variance and regression test, both with up to 5% probability of error by Software R (R Core TEAM, 2018). The phytometric characteristics of Cultivar BRS 394 were influenced by the doses of nitrogen: potassium and nitrogen: sulfur applied to the soil. Combinations of nitrogen doses from 187.86 to 262.22 kg ha-1 combined with potassium doses from 74.62 to 183.92 kg ha-1 , provide the best responses to the evaluated phytometric and productive variables. And the combinations of nitrogen doses from 204.83 to 265.49 kg ha-1 with sulfur doses ranging from 3.16 to 131.76 kg ha-1 , provide the maximum results of the analyzed variables. Thus, nitrogen fertilization influenced by doses of potassium and sulfur applied to the soil, provide the best results for the cultivation of wheat cultivar BRS 394 grown in Cerrado mato grossense.